Towards Revolutionizing Stem Education Via IoT and Blockchain Technology - Kamal, N.; H. Md Saad, M.; S. Kok, C.; Hussain, A. (International Journal of Engineering and Technology, 2018)
Internet of Things (IoT) has been implemented in most advance technologies as part of the emerging 4th industrial revolution, and recently, blockchain technology is being welcomed. These rapid growing technologies giving a big challenge to the students. As such, learning these new technologies should be made easy and simple. However, current education does not specifically offer a curriculum to empower skills and knowledge in IoT and blockchain technology. The aim of this research is to develop learning kit that can provide suitable training to understand concept of IoT and blockchain technology. The kit consists of three parts namely “brain”, “muscle” and “cloud”. Raspberry Pi is used as “brain” of operation that will be interact with the Caiser Cloud platform. A testbox operates as “muscle” to provide simple data input. The input from testbox will be sent, stored and displayed on a platform created using Xojo software. The results show that the learning kit is successfully interact with Caiser Cloud platform and can be used as a training tools for education purpose.
Keywords: Internet of Things (IoT); cloud platform; STEM education; blockchain technology.